DIODE LASER USED FOR TREATMENT OF ENDO-PERIO LESIONS IN A PATIENT HAVING HISTORY OF PULMONARY TUBERCULOSIS - Corina- Alexandra (Concită); Mihaela Sălceanu; Anca Melian; Raluca Dragomir; Cristian-Levente Giuroiu; Sorin Andrian (Romanian Dental Association for Education, 2021)
Oral tuberculosis lesions are the only manifestations of this disease that represents a real challenge for the clinician in terms of diagnosis. This clinical case presents a 58-year-old patient who came in for painful sensation when chewing and gingival bleeding around 1.4 tooth. Past medical history it reveals that she has pulmonary tuberculosis treated 6 months ago. At the time of the oral examination, the patient had no active pleuro-pulmonary lesions of pulmonary tuberculosis (TBP). By collaborating clinical examination and paraclinical data, we established the main diagnosis as beeing: endo-periodontal syndrome 1.4. We prescribed an associated treatment. We managed the periodontal support in a session (identification and quantification of periodontal pathogens in the red complex and also of the pathogen Mycobacterium tuberculosis by the qPCR Test method.) Ultrasonic supra- and subgingival scaling associated with 3% hydrogen peroxide irrigation and a session photodynamic therapy - diode were performed. Endodontic treatment was in two stages: mechano-chemical debridement in combination with irrigation with NaOCl 3% (ChloraxiD 3%), EDTA gel MD-CHELCREAM 19% and sonic activation of the irrigant, medicinal paste, then we performed the final root filling. Photodynamic therapy - diode afterwords. Coronary filling performed one week after the root filling. The probability that this endo-periodontal syndrome is a form of tuberculosis is very small. At the time of examination the patient did not have regional lymphadenopathy and no positive BK in the sputum or in the periodontal pouch present at tooth 1.4.